Campus no Nordeste: Reforma Universitária de 1968 - Câmpelo, Magda (2012)
Analysis of the urban architectural achievements of the federal universities of Ceara (UFC),Paraiba (URPB), Rio Grande do Norte (UFRN), Alagoas (UFAL), Maranhão (UFMA), Sergipe (UFS), and Piaui (UFPI) executed after the University Reform of 1968, designed to demonstrate that such university spaces, in their physical reformulation or constitution,according to the reformist project, adopted the standard of North American campus and produced urban and architectural configurations in the Northeast, with features highlighting responses submitted to the local context. The first part addresses the implementation of the University Reform and its features. It focuses on the campus model designed to meet the aims of efficiency and rationality of the university organization and the guidelines of the Manual by North American consultant Rudolph Atcon (1970), which was used as the basic document for its planning and execution. The second part addresses the creation of the seven universities. Based on an analysis matrix formulated from the recommendations of the Atcon Manual, the features are described and each campus is analyzed in accordance with the existing urban fabric, the urban and architectural conceptions, the constructive characteristic and the produced typologies, highlighting the rationalization aspects (standardization of the constructive elements), functionality (distribution of environments), modulation (structural or basis module) and flexibility (building relocation and expansion). Issues relating to the isolation or integration of the campuses in the urban structure, to the zoning as instrument of functional organization and as a segregation inductor, and to the limitation of procedures and constructive systems in the building rationalization concepts are examined forty years after the implementation of the Reform in 1968.